Atmospheric CO2 Capture by Microalgae Culturing: A Critical Review (GUB Journal of Science and Engineering, 2022)
With rising fuel demands, the carbon which is avowed as inefficient energy sources is continually declining. This method is a promiscuous way not of lowering CO2 emissions but of producing economic benefits. The physiochemical conversion of carbon dioxide into chemical (energy) goods without contamination. The production of microalgae will thus help to repair CO2 and biofuels sources. In this present work, we have done a comprehensive reviewed in this paper that carbon dioxide capture mechanism, contribution of microalgae for biomass production. As a result of using microalgae (S. platensis, Salmeriensis, and Scenedesmus dimorphus are capture maximum CO2 respectively of 1.00 and 0.81gL−1 d−1, 1.0gL−1day−1-2.8gL−1day−1 and 0.8g CO2 L−1d−1 with the production of microalgae biomass (